Tinjauan Proses Pembuatan Laporan Internal dan Pemanfaatan Informasi Rekam Medis Rumah Sakit Santa Elisabeth Medan - Robin Bastian Waruwu; Ita Monita Munthe (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Hospital reporting is an organizational tool that aims to be able to produce reports quickly, precisely and accurately. Types of reporting consist of internal and external reports. Based on the results of the research that the author did on internal reporting at the Santa Elisabeth Hospital Medan, there are still officers in the medical records unit who sometimes make mistakes in calculating the daily inpatient census recapitulation. With these errors, the report summary and the information needed are not appropriate. The purpose of this study was to review the process of making internal reports and the utilization of medical record information at Santa Elisabeth Hospital Medan. This study uses a descriptive method with a qualitative approach. In this study, officers in the medical records unit were interviewed by researchers to obtain hospital data. The place of implementation of this research is at Santa Elisabeth Hospital Medan which was held in July 2022. The results of this study indicate that: (1) The Medical Record Unit of Santa Elisabeth Hospital Medan has carried out the medical record data processing properly starting from assembling, coding, indexing, filling and report generation to produce useful information for hospitals. (2) The daily census procedure for inpatients at Santa Elisabeth Hospital Medan has a percentage of 95% and is categorized as appropriate, while the daily census recapitulation for inpatients has a percentage of 79% and is categorized as less appropriate. (3) Medical record information is used for internal hospital reports, as material for determining the cost of paying for hospital services, the basis for planning treatment/care that must be given to patients, material for decision making, hospital leadership considerations and also used for research and education.